2015
DOI: 10.3791/52611
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Meshwork Response to Pressure Elevation in the Living Human Eye

Abstract: The mechanical characteristics of the trabecular meshwork (TM) are linked to outflow resistance and intraocular pressure (IOP) regulation. The rationale behind this technique is the direct observation of the mechanical response of the TM to acute IOP elevation. Prior to scanning, IOP is measured at baseline and during IOP elevation. The limbus is scanned by spectral-domain optical coherence tomography at baseline and during IOP elevation (ophthalmodynamometer (ODM) applied at 30 g force). Scans are processed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…For example, behavior of TM/SC can be monitored at different IOP levels (Li et al, 2014a; Li et al, 2014b) and at different disease stages (Li et al, 2014b). Similar to healthy human volunteers (Kagemann et al, 2015), we observed that mouse SC dimensions are reduced in a pressure-dependent manner that is quickly reversible (Li et al, 2014a; Li et al, 2014b). The mouse eyes also respond to topical cholinergic treatment similarly to that of human eyes (Flocks and Zweng, 1957; Li et al, 2014a; Lutjen-Drecoll, 1973), with the ciliary muscle contracting to maintain a patent conventional outflow tract (Li et al, 2014a).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…For example, behavior of TM/SC can be monitored at different IOP levels (Li et al, 2014a; Li et al, 2014b) and at different disease stages (Li et al, 2014b). Similar to healthy human volunteers (Kagemann et al, 2015), we observed that mouse SC dimensions are reduced in a pressure-dependent manner that is quickly reversible (Li et al, 2014a; Li et al, 2014b). The mouse eyes also respond to topical cholinergic treatment similarly to that of human eyes (Flocks and Zweng, 1957; Li et al, 2014a; Lutjen-Drecoll, 1973), with the ciliary muscle contracting to maintain a patent conventional outflow tract (Li et al, 2014a).…”
Section: Introductionsupporting
confidence: 59%
“…Major advancements in OCT technology for the anterior eye have resulted in increased reproducibility and accuracy in the assessment of progressive tissue damage (Kagemann et al, 2015; Li et al, 2007) and enhanced penetration of the OCT signal into ocular tissues, including conventional outflow structures (Francis et al, 2012; Kagemann et al, 2014a; Kagemann et al, 2010). Interest in imaging the trabecular meshwork/Schlemm’s canal (TM/SC) has increased in recent years since reduced aqueous humor drainage through these tissues is the root cause of ocular hypertension in glaucoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of the extracellular matrix caused fibrosis and increased stiffness of the TM. TM stiffness that could influence the extent of deformation of TM and the inner wall of SC [ 45 47 ]. Using atomic force microscopy, Last et al [ 48 ] found that the elastic modulus of the TM was higher in eyes with glaucoma than in normal eyes, suggesting an increased TM stiffness in eyes with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…When the investigators disagreed on the delineation of SC, a mutual conclusion was reached after discussion. These parameters were then measured by a masked, experienced investigator (YS) using ImageJ software (version 1.47, National Institutes of Health, Bethesda, Maryland, USA) transformed from pixel to anatomic values as previously described [16]. SS was defined as the end point of the curved interface between the ciliary body and the sclera/ TM based on previous studies [17].…”
Section: Image Processingmentioning
confidence: 99%